Trained dogs can identify malignant solitary pulmonary nodules in exhaled gas. (September 2019) - Guirao, A.; Molins, L.; Ramón, I.; Sunyer, G.; Viñolas, N.; Marrades, R.; Sánchez, D.; Fibla, J.J.; Boada, M.; Hernández, J.; Guzmán, R.; Libreros, A.; et al.
Graphical abstract: Highlights: Exhaled air LC detection by trained dogs has high diagnostic rate (incl. tumors <3 cm). Canine LC detection enables research on olfaction-based pattern analysis techniques. Combinatorial selectivity, present in nature, enables multi-molecule identification. This strategy could be replicated in olfaction-based detection devices. Until device development, trained dogs could be the detection standard practice. Abstract: Objectives: To investigate the capacity of a trained dog to identify LC in patients with malignant SPN. Methods: We collected 90 exhaled gas samples from 30 patients with SPN (3 samples/patient). As controls we used 61 healthy volunteers and 18 COPD patients without SNP or LC, in each of whom we collected 5 exhaled gas samples (n = 395). The dog (Blat, a 4-year-old crossbreed between a Labrador Retriever and a Pitbull) and the methodology used were the same as previously reported by our group (see: https://drive.google.com/open?id=1R4mOtOtuZkTeb5iOEEv0K9r2kHKlPhWd ). Results: Of 30 patients with SPN, Blat recognized 27 of them as positive for LC and 3 as negative for LC. These results fully matched post-surgical pathological results. Sensibility was 0.97, Specificity 0.99, Positive Predictive value 0.97 and negative predictive value 0.99. The AUC of the ROC curve was 0.985. Conclusions: Trained dogs can identify accurately the malignant origin of SPN. It is now time to develop technology that can match canine olfaction and facilitate the implementation of this diagnostic approach in the clinic.